2020
DOI: 10.1007/s00234-020-02531-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparing extended versus standard time window for thrombectomy: caseload, patient characteristics, treatment rates and outcomes—a prospective single-centre study

Abstract: Purpose New guidelines recommend thrombectomy up to 24 h in selected patients; however, the workload and benefit of extending time window are not known. We conducted a prospective single-centre study to determine the caseload, imaging and interventional need of extended time window. Methods All consecutive ischemic stroke patients within 24 h from onset in an 11-month period were included. Thrombectomy eligibility in the 0–6 h time window was based on current guidelines; in the 6–24 h time window, it was bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Both RCTs demonstrated the superiority of MT to standard care in eligible patients. The findings translated well into daily practice: large retrospective studies found MT to be effective and safe even with the application of less strict selection criteria [ 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 76%
“…Both RCTs demonstrated the superiority of MT to standard care in eligible patients. The findings translated well into daily practice: large retrospective studies found MT to be effective and safe even with the application of less strict selection criteria [ 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 76%
“…Since extending the therapeutic window from 6 to 24 h may result to an increase up to 27% in patients receiving EVT, the importance of recent late time window RCTs becomes evident. 72 It should be noted that the HERMES meta-analysis showed that benefit of EVT using standard neuroimaging remains statistically significant up to 7 h and 18 min from LSW. This temporal cut-off has been adopted by the 2019 joint ESO and European Society for Minimally Invasive Neurological Therapy (ESMINT) EVT Guidelines.…”
Section: Endovascular Treatment In the Anterior Circulation Before An...mentioning
confidence: 96%
“…Mechanical Thrombectomy (MT) has established its efficacy as a primary treatment for acute ischemic stroke with large vessel occlusion (AIS-LVO), providing substantial benefits, especially within the initial 6-h therapeutic window (Wahlgren et al, 2016;Bhan et al, 2020). However, a significant proportion of AIS-LVO patients, estimated to be approximately 30-40%, present to care facilities beyond this traditional window, specifically between 6 and 24 h from symptom onset (Jadhav et al, 2018;Gunda et al, 2021). While the DEFUSE 3 (Endovascular therapy following imaging evaluation for ischemic stroke 3) and DAWN (Diffusion-weighted imaging or computerized tomography perfusion assessment with clinical mismatch in the triage of wake up and late presenting strokes undergoing neurointervention with Trevo) trials have indicated the potential benefits of MT in this extended time window, they also highlighted the variability in outcomes (Jabal et al, 2023;Zhan et al, 2023), with beneficial functional outcomes at 90 days observed in roughly 45 and 49% of patients, respectively (Albers et al, 2018;Nogueira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%